Cosmetovigilance: a review and practice in India - Sahu, Shashank; Singhal, Ankita; Bhardwaj, Abhijit (International Journal of Basic & Clinical Pharmacology, 2025)
Cosmetovigilance is a rapidly expanding area of research under pharmacovigilance in India. This study analyses the cosmetic consumption practices and associated adverse drug reactions reported by particulars. According to the US Food and Drug Administration’s (FDA), cosmetics are defined as ‘article for beautification, cleansing or altering physical appearance’ (U.S. Food and Drug Administration, 2018). The consumption of personal care products (PCP) has been rising for quite a while in passing decades which something has to do with physical appearance in the community globally which directly gave rise to emergent of cosmetic industries. Their continuous exposure could lead to significant accumulation in the body and for several adverse health outcomes which can appear as redness, scales and blisters, marking to no visible changes whereas major manifestation can range up to loss of hair, fragile nails and contact dermatitis. Data suggest hair dye is one of the leading causes for contact dermatitis in India. Counterfeit cosmetics is fraudulent or imitation beauty products that are designed to mimic genuine and reputable brands. These counterfeit products are often produced and distributed without the authorization or approval of either original brand or regulatory bodies. Impurities such as high level of heavy metals (lead, cobalt cadmium, mercury and aluminium) are reported in many cosmetics products (lipstick, lip glosses, eye shadow and hair dye) while they pose peculiar health threats like hand dermatitis, asthma and infertility, which is common among hair and saloon technicians.